The Role of Civics in Forming Citizens with Pancasila - Achmad Zurohman; Babul Bahrudin (Journal Civics And Social Studies, 2021)
This research discusses the role of citizenship education in creating citizens who are active in carrying out their duties and responsibilities as good citizens in accordance with Pancasila values. The aim of this research is to examine the role of citizenship education in forming Pancasila citizens. This research uses a literature study method. The approach is carried out with content analysis. In the stages, data is collected from various types of literature, analyzed, assessed, and finally conclusions are drawn. The research findings conclude that Citizenship Education plays a very important role in forming citizens with Pancasila, including providing valid and correct understanding, knowledge and comprehension, laying down and instilling patterns of thought (Fattern of thought) in accordance with Pancasila and Indonesian character, instilling Pancasila moral values ​​into students, raising the awareness of Indonesian citizens and society to always maintain and preserve Pancasila moral values, providing motivation so that every attitude and behavior grows in accordance with Pancasila values ​​and norms.